Elevated temperature tensile and bending strength of ultra-high temperature ceramic matrix composites obtained by different processes. Issue 11 (September 2023) - Galizia, Pietro; Sciti, Diletta; Binner, Jon; Venkatachalam, Vinothini; Lagos, Miguel.A.; Servadei, Francesca; Vinci, Antonio; Zoli, Luca; Reimer, Thomas
Abstract: This paper presents a comparison of microstructures and mechanical properties of different ZrB2 -based CMCs, which were manufactured in the frame of the Horizon 2020 European C 3 HARME research project through different processes: slurry infiltration and sintering (SIS), polymer infiltration and pyrolysis (PIP) and radio frequency chemical vapour infiltration (RF-CVI). Tensile testing with a novel optimized shape of the specimens was performed and compared with the results of flexural tests to assess the structural properties. For the first time, tensile tests up to 1600 °C were carried out on UHTCMCs. Despite the different microstructural features, all the ZrB2 -based CMCs demonstrated excellent structural properties even at elevated temperature. The characterization shows how the different amount of porosity and fibre properties, such as its stiffness, strength and elongation, affected the mechanical behaviour of the C 3 HARME's composites. Finally, the role of the high level of residual thermal stresses is discussed.